Effect of solid-state fermentation on kidney bean flour: Functional properties, mineral bioavailability, and product formulation - Nikhil Dnyaneshwar Patil; Aarti Bains; Gulden Goksen; Nemat Ali; Sanju Bala Dhull; Mohammad Rashid Khan; Prince Chawla (Food Chemistry: X)
This research investigated the effects of solid-state fermentation with Aspergillus awamori (MTCC 548) on the mineral bioavailability, structural characteristics, and functional attributes of kidney bean flour across different fermentation durations (24–96 h). Notable improvements were observed during 96 h of fermentation, including significant increases in foaming capacity and stability (by 32.30 % and 34.81 %), emulsifying capacity and stability (by 32.67 % and 47.37 %), oil and water holding capacities (by 72.86 % and 61.87 %, respectively). Bulk density decreased by 48.68 %. Fermented samples demonstrated structural changes and chemical alterations with increased thermal stability at 24 and 48 h, which declined with extended fermentation. The iron and zinc contents increased by 5.95 % and 13.59 %, respectively, after 24 h, with bioavailability improving by 34.53 % and 36.30 %. Additionally, the fermented kidney bean flour enhanced the in-vitro digestibility of biscuits by 31.33 %. This study highlights the potential of solid-state fermentation to enhance the nutritional and functional properties of kidney bean flour.